NEEDLE RENAL LIFTING TECHNIQUE IN MANAGEMENT OF COMPLICATED PROXIMAL URETERAL LITHOTRIPSY: A CASE REPORT - Risan, Muhammad; Soeroharjo, Indrawarman; Danarto, Raden; Yuri, Prahara (Indonesian Journal of Urology, 2021)
Objective: To described a needle renal lifting technique using an 18-gauge needle to adjunct ureterorenoscopy (URS) in the management of complicated proximal ureteral stones. Case(s) Presentation: A 46 years old man presented with right flank pain for 1 month. This patient was diagnosed with ureteral stone and ureteral kinking that prohibits access to the proximal side of the ureter. Due to difficult access to the proximal ureter, we perform a needle renal lifting technique which is initialized by puncturing the middle renal calyx with 18-gauge needle. Then, the proximal end of the needle was pushed to the caudal direction to move the kidney to the cephalic direction and straighten the kinked ureter. After that procedure, the URS sheat can easily enter the proximal ureter to the stone site. Discussion: The success rate of this procedure is based on the operator skills to access the calyx and perform URS simultaneously. Like a previous technique, needle renal lifting is effective only when the kidney is mobile. Conclusion: The needle renal lifting technique can be used to adjunct URS in the management of complicated ureteral stones which prohibited access to the proximal ureter.